Training on the Production of Catfish (Clarias sp.) Pempek Fortified with Tempe Flour (Rhizopus sp.) - Urbanus Sihotang; Novriani Tarigan (FKM UIN Sumatera Utara Medan, 2026)
Snack foods are an inseparable part of the daily dietary pattern of school-aged children because they are practical, easily accessible, and affordable. However, most school snacks available have low nutritional quality, being high in carbohydrates and fats while low in protein and essential micronutrients. This condition may lead to excessive macronutrient intake and contribute to an increased risk of overnutrition and overweight. The objective of this community service activity was to improve mothers’ knowledge and skills in providing nutritious snack foods through the preparation of catfish pempek (Clarias sp.) with the addition of tempeh flour (Rhizopus sp.). The activity was conducted at the Nogorejo Village Community Hall, Galang Subdistrict, on July 31, 2025. The preparation stage included obtaining permits, coordinating with the PKK leader to determine participants and the schedule, developing leaflets, and conducting trial production of pempek in the food technology laboratory of the nutrition department. The implementation stage consisted of nutrition education on healthy snacks, explanation and demonstration of pempek preparation, product tasting, and preference evaluation. Participants included 30 PKK members, Posyandu cadres, mothers of toddlers, and mothers of school-aged children. The results showed high participant enthusiasm, demonstrated by a quiz of four questions that were all answered correctly. Evaluation indicated that all participants found the activity useful and satisfying. Sensory evaluation showed 100% acceptance of taste, aroma, and texture, although 10% disliked the aroma due to a fishy smell.